Sosialisasi Lingkungan Fisik terhadap Kesehatan Masyarakat di Kampung Penggilingan Baru RT.003/RW.008 - Adinda Evriyaza Putri; Azzahra Rahmita; Djedidja Agnessanda Sihaloho; Reni Wahyu Mustika; Vira Khoirunnisa; Rijal Abdillah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This study aims to analyze the influence of socialization of the physical environment on public health in Penggilingan Baru Village RT. 003/RW. 008, Harapan Baru, with an emphasis on preventing and treating infectious diseases caused by floods. The method used in this research is macro social intervention, which involves direct outreach to residents to increase awareness about environmental cleanliness. The findings from this research indicate that the physical environmental conditions in this area still require special attention, especially in the management of irregular air drainage channels. Stagnant water that occurs regularly after heavy rain increases the risk of flooding and the emergence of infectious diseases such as diarrhea and dengue fever. Outreach to the community to carry out environmental cleanliness with monthly community service activities and waste sorting, to be implemented in stages. The conclusion of this research is that socialization of the physical environment through a macro social intervention approach can contribute to reducing the risk of infectious diseases by increasing public awareness of the importance of maintaining environmental cleanliness. The recommendations provided include improving the drainage system, more coordinated waste management, and ongoing education to create a healthier environment.